The acceptability of a novel procedure service run by PAs and NPs. Issue 12 (December 2021) - Kim, Nancy; Herbert, Tara; Marranca, Sheyla; Bergman, Eric; Castillo, Ronald; Romano, Lindsey; Heacock, Daniel; Cushing, William
ABSTRACT: Background: Hospitalist physicians are performing fewer procedures because of multiple reasons, including expanded responsibilities beyond their patient panel. A procedure service that offloads hospitalists could expedite these necessary services. An opportunity exists for physician assistants (PAs) and NPs to fill this gap. Objective: To describe the implementation of a PA- and NP-run procedure service at a large academic hospital. Methods: This is a retrospective cohort study of procedures by the procedure service at one institution from 2015 to 2019. Results: Over 5 years, 7, 002 procedures were performed, with requests increasing over time. The most frequent procedures were venous access, lumbar puncture, paracentesis, and placement of nasogastric or nasojejunal tubes. Requesting services included hospitalists and residents from internal medicine, surgery, and neurology. Conclusions: A PA- and NP-run procedure service is well accepted at a large academic hospital despite the lack of involvement by attending physicians. Future directions are focused on augmenting coverage and procedures offered.